2007
DOI: 10.1007/s10750-007-9148-4
|View full text |Cite
|
Sign up to set email alerts
|

Blackfly assemblages (Diptera, Simuliidae) of the Carpathian river: habitat characteristics, longitudinal zonation and eutrophication

Abstract: Investigations were carried out in 2003-04 within a project on trend biomonitoring of macrozoobenthos in the Hron River system. They were focused on blackfly assemblages of the Hron River (Slovakia), using the distribution patterns of blackflies (18 species) from 14 sites, representing a fluent transition from epirithral to epipotamal. Two main ''sister'' groups were distinguished using TWINSPAN analysis. Prosimulium rufipes is an indicator species within the first group. This group typically occurs in the zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
4
16
0
Order By: Relevance
“…For these reasons, we tried to delineate distinct biotic zones of the Hron River and used caddisfly species as indicators of those zones. Along with the results provided elsewhere (Bitušík et al, 2006;Krno, 2007;Illéšová et al, 2008) we obtained important information on predisturbance longitudinal patterns in benthic assemblages of the Hron River. Dams affect the sediment dynamics and distribution, dispersal, and abundance of benthic macroinvertebrates and other aquatic organisms (Stanford et al, 1996;Kiraly et al, 2014).…”
Section: > River Zonation As a Reference Schemesupporting
confidence: 64%
See 1 more Smart Citation
“…For these reasons, we tried to delineate distinct biotic zones of the Hron River and used caddisfly species as indicators of those zones. Along with the results provided elsewhere (Bitušík et al, 2006;Krno, 2007;Illéšová et al, 2008) we obtained important information on predisturbance longitudinal patterns in benthic assemblages of the Hron River. Dams affect the sediment dynamics and distribution, dispersal, and abundance of benthic macroinvertebrates and other aquatic organisms (Stanford et al, 1996;Kiraly et al, 2014).…”
Section: > River Zonation As a Reference Schemesupporting
confidence: 64%
“…All of the lower section of the river can be classified as epipotamal. Previous efforts to distinguish discrete zones of the Hron River based on chironomids (Bitušík et al, 2006) and blackflies (Illéšová et al, 2008) revealed slightly different schemes (Figure 6). The most apparent change in caddisfly communities was observed at the river section where filtering caddisflies become dominant, probably mirroring changes in food supply.…”
Section: > River Zonationmentioning
confidence: 93%
“…Authors confirmed 16 species of blackflies at four sites. Illéšová et al found 9 species in Zubrovica stream [13], which belongs to investigated flows of our research as well. There were 11 species found in the upper section of the Hron River near Telgárt.…”
Section: Introductionsupporting
confidence: 68%
“…Urbanization and agricultural land use affect the community structure and biodiversity of black flies (Adler et al 2004;Zhank et al 1998). Changes in species composition can indicate longitudinal zonation and eutrophication (Halgoš et al 2001;Illéšová et al 2008). Schreder & Waringer (2002) found that species richness of black flies in European streams increased with current velocity and the size of streambed particles.…”
Section: Introductionmentioning
confidence: 99%